Reducing emission of NOx and SOx precursors while enhancing char production from pyrolysis of sewage sludge by torrefaction pretreatment - Anqing Zheng (2020)
© 2019 Elsevier Ltd This study aims to explore the possibility of reducing emission of NOx and SOx precursors while enhancing char production from pyrolysis of sewage sludge by torrefaction pretreatment. The influence of torrefaction severity on structural alterations of sewage sludge and resulting pyrolysis behaviors was systematically studied. The experimental results show that 33.3% of N and 52.8% of S in sewage sludge can be removed by torrefaction pretreatment, leading to the evident reduction in the emission of NOx and SOx precursors (e.g. NH3, HCNO, H2S, COS and CS2) during subsequent pyrolysis of torrefied sewage sludge. Moreover, the yield and specific surface area of char from pyrolysis of sewage sludge can be improved by torrefaction. The char obtained from pyrolysis of sewage sludge torrefied at 300 °C exhibited the highest yield of 61.0 wt% and the maximum BET surface areas of 26.5 m2/g. These results could be ascribed to the devolatilization, polycondensation and charring of sewage sludge during torrefaction to form torrefied sewage sludge with stable aromatic and heterocyclic structure. These findings suggest that torrefaction is an effective pretreatment method prior to pyrolysis of sewage sludge for reducing emission of NOx and SOx precursors while enhancing yield and specific surface area of char.